Sharia Finance Training in Increasing the Capacity of Human Resources in the Savings and Loan Cooperative Ar-Rohmah Sidoarjo - Renny Oktafia; Mentari Clara Dewanti (LPPM Universitas Yudharta Pasuruan, 2022)
The Ar-Rohmah Savings and Loans Cooperative is transitioning from conventional cooperatives to sharia-based cooperatives, to meet the demands of cooperative members that are under Islamic values ​​and are more just in transactions under muamalah provisions in Islam. Therefore, to help with the problems faced by the East Java Ar Rohmah Savings and Loans Cooperative and increase the capacity of its human resources, it is necessary to hold training related to Islamic financial management. This activity aims to provide training to employees of the Ar-Rohmah Savings and Loan Cooperative on how to manage finances according to sharia principles so that later they can serve customers well under Islamic sharia provisions. The implementation of this activity uses the Participatory Action Research method through three stages, namely preparation, implementation, and evaluation. Through the evaluation results of the pre-test and post-test with a ratio of 11.91, this community service activity has succeeded in changing the work habits of cooperative employees towards the work and knowledge they apply. The knowledge that has been obtained regarding Islamic financial management is expected to become a driving force for other Islamic cooperative employees.